New expressions of urban centralities and socio-spatial differentiation: a look through spatial practices - Anastácio Alves da Silva, Késia; Moura de Lacerda Teixeira, Vanessa; Savério Sposito, Eliseu (Geografares, 2021)
Contemporary cities have been permeated by the emergence of new commercial and service concentration areas and the density of flows towards these zones, which characterized the emergence of new expressions of centralities. This article aims to analyze the socio-spatial differentiation in uses and appropriation of the urban centres by individuals who live in habitats aimed at the middle and elite classes. Two middle-sized cities in São Paulo State are the case study: Ribeirão Preto and Presidente Prudente. The emergence of new centralities is analyzed through the distribution of trade and service activities. Frequency, preferences, and motivations for carrying out socio-spatial practices in certain central areas, interviews, clarify the understanding of the segmentations that characterize the production of centralities in the context of contemporary urbanization.